KETERLIBATAN KERJA,KECERDASAN EMOSIONAL DAN KEADILAN ORGANISASI TERHADAP INOVASI INDIVIDU PADA GURU DI PASIR PENGARAIAN - Devi Novianti; Ummul Khoiri (Jurnal Bina Wira, 2024)
This study aims to determine the simultaneous effect of work involvement, emotional intelligence and organizational justice on individual innovation. The research method used is a quantitative method, the population in the study is teachers in Pasir Pengaraian with an unknown number. The sampling technique method uses a random sampling method of 99. and the data analysis technique used is descriptive analysis and multiple linear regression analysis. The results of the study from multiple linear regression obtained the regression equation Y = 9.241 + 0.098X1 + 0.048X2 + 0.655X3, the coefficient of determination obtained an R value of 0.692, the results of the study from the t test of the work involvement variable showed Tcount 0.887 <ttable = 1.66071, the emotional intelligence variable showed tcount = 0.044 <ttable = 1.66071, the results of the F test showed the Fcount number obtained was 29.020> Ftable of 2.47